Complete mitochondrial genome sequences of the Arctic Ocean codfishes Arctogadus glacialis and Boreogadus saida reveal oriL and tRNA gene duplications - Breines, Ragna; Ursvik, Anita; Nymark, Marianne; Johansen, Steinar; Coucheron, Dag-Hugo (Polar Biology, 2008)
We have determined the complete mitochondrial genome sequences of the codWshes Arctogadus glacialis and Boreogadus saida (Order Gadiformes, Family Gadidae). The 16,644 bp and 16,745 bp mtDNAs, respectively, contain the same set of 37 structural genes found in all vertebrates analyzed so far. The gene organization is conserved compared to other Gadidae species, but with one notable exception. B. saida contains heteroplasmic rearrangement-mediated duplications that include the origin of light-strand replication and nearby tRNA genes. Examination of the mitochondrial control region of A. glacialis, B. saida, and four additional representative Gadidae genera identiWed a highly variable domain containing tandem repeat motifs in A. glacialis. Mitogenomic phylogeny based on the complete mitochondrial genome sequence, the concatenated protein-coding genes, and the derived protein sequences strongly supports a sister taxa aYliation of A. glacialis and B. saida.